Assessment of the effectiveness of three different cephalosporin/clavulanate combinations for the phenotypic confirmation of extended-spectrum beta-lactamase producing bacteria isolated from urine samples at National Public Health Laboratory, Kathmandu, Nepal. (December 2016) - Bhandari, Raju; Pant, Narayan; Poudel, Asia; Sharma, Mukunda
Abstract Background The extended-spectrum β-lactamase (ESBL) producing bacteria are present as the serious public health problems due to their resistance to large number of antibiotics. The main aims of this study were to determine the prevalence and antibiotic resistance patterns of bacteria producing extended-spectrum β-lactamases (ESBLs) and to find the suitable cephalosporin/clavulanate combination for phenotypic confirmation of ESBL production. Methods During the study period from April 2013 to November 2013, a total of 1003 urine samples from the patients visiting National Public Health Laboratory, Kathmandu, Nepal were collected and processed. The isolates were identified with the help of colony characteristics, gram stain and conventional biochemical tests. Antimicrobial susceptibility testing was performed by Kirby Bauer disc diffusion method. ESBL production screening was done by using ceftriaxone, while ESBL production confirmation was done by using three different 3rd generation cephalosporin/clavulanate combinations. Results Of the 138 isolates, Escherichia coli was the most predominant with 88 (63.8 %) isolates. Among the antibiotics tested for gram negative bacteria, highest susceptibility was seen toward imipenem followed by amikacin. Of the total isolates, 68 (49.3 %) were suspected as ESBL producers. Of these, 44 (64.7 %) were phenotypically confirmed to be ESBL producers. The majority of ESBL producers wereE. coli with 34 (72.3 %) isolates. Of the three different 3rd generation cephalosporin/clavulanate combinations used, ceftazidime/clavulanate combination was found to be most effective for phenotypic confirmation of ESBL producers and was statistically highly significant (P < 0.01). Conclusion Based on the findings of our study, we recommend to use ceftazidime/clavulanate combination for phenotypic confirmation of ESBL producers. Routine ESBL testing for uropathogens along with conventional antibiogram would be useful for proper early management of all the cases of urinary tract infections.